Adaptación del cuestionario de crianza parental (pcri-m) en Canto Grande - Becerra , Sara (2022)
The adaptation of the Parental Upbringing Questionnaire (PCRI-M), which measures the attitudes of the parents toward the upbringing of the children, distributed over scales of support, satisfaction in upbringing, commitment, communication, discipline, autonomy, role distribution and social desirability are presented in this document. It was applied to 375 mothers of Canto Grande whose ages range between 26 and 53. The results indicate that the characteristics of the questionnaire are adequate and can therefore be used with this type of population. Likewise, there are cross-cultural differences in attitudes toward upbringing between Spanish mothers and those of Canto Grande.